Estudo retrospectivo e prospectivo dos tumores cutâneos em cães e diferenciação dos tumores cutâneos de células redondas pela imuno- histoquímica - Marina Rios de Araujo (2011)
The objectives of this study were to determine the prevalence of skin tumors in dogs, to relate the histological type with the anatomical location, and to use the immunohistochemistry (IHC) to differentiate the "round cell tumors. Also, was evaluated the expression of CD117 in mast cell tumors (MCT) and compare it with the histological grades, in primary and metastatic MCT. The dogs diagnosed with round cell tumors in the Veterinary Hospital of UFMG during 2009 to 2010 period were also investigated about treatment, recurrence and/or metastases. The evaluation was performed by analysis of the protocols of a skin biopsy and necropsy records of skin tumors archived in the Veterinary Pathology Laboratory of the Veterinary School during 1996 to 2010 period. The markers CD117, CD3, CD79a, CD45, vimentin, E-cadherin and cytokeratin AE1/AE3 were used in this study. A total of 1762 dogs and 1882 skin tumors were found. The most common tumors in young animals were histiocytoma, MCT and papilloma. The anatomical location in descending order of frequency was head (18.25%), perineum (10.23%), thorax (8.76%), pelvic limb (7.71%), forelimb (7.45%), abdomen (6.30%), back (5.35%), scrotum (3.36%), neck (2.94%), prepuce (2.57%) and tail (1.57%). Approximately 8.50% of the animals had multifocal tumors. Malignant neoplasms were more frequent than benign. Approximately 45.59% of the neoplasms were mesenchymal, 42.74% were epithelial, 8.91% were melanocytic and 1.57% were hematopoietic. After IHC tests, the frequency of round cells tumors was modified. Thus, 315 were diagnosed as MCT, 40 as lymphomas, 38 as cutaneous histiocytomas, 13 as transmissible venereal tumors (TVT), 9 as plasm cell tumors and 6 as localized histiocytic sarcomas. The ten most prevalent tumor types were: MCT (16.73%, 315/1882), melanoma (9.03%, 170/1882), lipoma (7.49%, 141/1882), sebaceous adenoma ( 6.53%, 123/1882), squamous cell carcinoma (6.42%, 121/1882), hepatoid adenoma (5.89%, 111/1882), hemangiosarcoma (4.94%, 93/1882), hemangioma (3.77%, 71/1882), trichoblastoma (2.39%, 45/1882) and fibrosarcoma (2.12%, 40/1882). Of 78 MCT without metastasis identified by the IHC, 43.59% were classified histologically as grade I, 34.62% as grade II and 21.79% as grade III. Simultaneously, 53.85% were classified as standard KIT I, 30.77% as standard KIT II and 15.38% as standard KIT III. In these 78 MCT evaluated, there were no statistical significant differences between the histological grades for the three standards KIT. The standard KIT of 16 metastatic MCT was also evaluated and no statistical significance between the primary tumor and metastases was detected. The correlation between the pattern of KIT and its corresponding primary tumor metastasis was 78%. The average of recurrent free period in 25 animals diagnosed with MCT was 325 days, regardless of grade, standard KIT or treatment. The mean disease-free survival time in the five animals diagnosed with T cell lymphoma was 225 days.